SIG na saúde pública - estudo de caso: mortalidade infantil em Dom Pedrito/RS - Leon, Maria Elaine dos Santos (2007)
This assignment has the objective to socialize some knoledges about the analysis of space distribution of children´s mortality in municipality of Dom Pedrito, connecting with the health service existing, like the urban and social organization finded. It was used a Geografic Information System (GIS), through of the geographic map´s study of Dom Pedrito, with the database of the 7th Health´s Regional Coordinate, these secundary pieces (already existing) of the children´s mortality in the municipality occurred in the urban zone, from 1998 to 2004.The possibility of the space´s analysis of this indicator through the geoprocessing techniques is of extremely mportance, ´cause to serve as support to the decisions´ conquest, reinforcing the idea that the children´s mortality is connected with the sanitary and social questions related with the people´s life conditions, because the geographic distribution of the happenings is locate basically in the town´s outskirt, where the conditions are poor in relation to the urban´s infrastructure, where the offered services are lacker and like this become the people more vulnerable.